The contribution of short-waves in storm surges: Two case studies in the Bay of Biscay. (15th March 2015) - Bertin, Xavier; Li, Kai; Roland, Aron; Bidlot, Jean-Raymond
Abstract: This study investigates the contributions of short waves in storm surges through the hindcast of two storms that hit the central part of the Bay of Biscay recently. Despite displaying comparable wind speed and directions in the study area, these two storms induced different storm surges and sea states. Xynthia (27–28th of February 2010) was characterized by large (up to 7 m significant wave height H s ) and short-period waves and induced an exceptional storm surge, locally larger than 1.6 m. The second storm, Joachim (15–16th of December 2011), was characterized by very large (up to H s >10 m) and long-period waves but only induced a storm surge almost two times lower. To investigate these differences, a new unstructured grid and fully coupled modeling system is applied, with a spatial resolution fine-enough to adequately represent the surf zones over most of the study area (25 m). The analysis of the modeling results and the available field observations reveals firstly that the exceptional surge during Xynthia originated from young and steep waves, enhancing surface stress. This particular sea-state is explained by the abnormal track of Xynthia, which restricted the fetch to a few hundred km. The wave radiation stress gradient locally induced setup larger than 0.4 m along the coastlines fully exposed to ocean waves, while wave setup in the range 0.1–0.2 m was also shown to develop regionally and to propagate in sheltered harbors. Comparatively, wave-enhanced bottom stress appears to be a second-order process and has a more limited impact on storm surges. Highlights: High resolution hindcast of sea-states and storm surge associated with Xynthia and Joachim. Sea-state can enhance surface stress strongly. Wave setup can propagate outside surf zones.